PENGARUH PENDAPATAN, LITERASI KEUANGAN DAN KONTROL DIRI TERHADAP PERILAKU KONSUMTIF MAHASISWA DI SURAKARTA - Agata Safira Rahma Dany; Ari Susanti (Bajang Institute, 2023)
This study aims to analyze and measure the effect of income, financial literacy and self-control in students on consumptive behavior. This study uses quantitative descriptive analysis techniques. This research uses an unlimited size or an unknown number because of the large number of active students in universities throughout in Surakarta. Sampling using purposive sampling technique amounted to 100 respondents using the Hair formula. The results obtained are income and self-control in stud ents affect consumptive behavior, while financial literacy in students does not affect consumptive behavior.